The Concept of Diversion as a Measure to Address Children in Conflict with the Law - Al Basya; M. Arif; Iqra Lugan Sakrora; Ferlan Niko (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to describe the position of diversion in the resolution of cases involving children. The handling of cases involving children differs significantly from those involving adult offenders; the process must take the child's psychological state into account to avoid causing further trauma. This study employs a library research method—a scientific approach that focuses on examining written sources as primary data. A qualitative approach is utilized, with data gathered from various literature sources, including law books, articles, scholarly papers, and online resources. Data analysis is conducted using an inductive method. The findings indicate that child protection is a shared responsibility involving parents, the community, the government, and the state. While every effort should be made to prevent children from coming into contact with the legal system, if such contact occurs, the case resolution process must prioritize the child's status and psychological well-being. For children facing legal issues or criminal charges, it is crucial to prioritize a resolution method commonly known as "diversion." Maximizing the use of diversion is a vital step toward ensuring optimal protection for children.